Improvement of an anterior infrabone defect using combined periodontal and orthodontic therapy: a 6-year follow-up case report - Molon, Rafaelscaf de [UNESP]; Kim, Yeon Jung; Santos-Pinto, Arydos [UNESP]; Cirelli, Joni Augusto [UNESP] (Thieme, 2014)
Extensive intraosseous lesions represent a clinical challenge for the periodontist. Sites with bone defects have been shown to be at higher risk of periodontitis progression in patients who had not received periodontal therapy. Thus, the aim of this case report was to describe a novel approach for the treatment of 1-walled intraosseous defect by combining nonsurgical periodontal therapy and orthodontic movement toward the bone defect, avoiding regenerative and surgical procedures. A 47-year-old woman underwent the proposed procedures for the treatment of her left central incisor with 9 mm probing depth and 1-walled intraosseous defect in its mesial aspect. Initially, basic periodontal therapy with scaling and root planning was accomplished. Two months later, an orthodontic treatment was planned to eliminate the intraosseous lesion and to improve the interproximal papillary area. Orthodontic root movement toward the osseous defect was performed for 13 months with light forces. After 6 years postoperative it was concluded that combined basic periodontal therapy and orthodontic movement was capable of eliminating the intraosseous defect and improve the esthetics in the interproximal papillary area between the central incisors.
Keywords: Interproximal papillary area; Intraosseous bone defect; Periodontal treatment; Periodontitis; Tooth movement